Handbook of Research on Coping Mechanisms for First-Year Students Transitioning to Higher Education: - Odhiambo, Janet Auma; Aloka, Peter J.; Aomo, John Agwaya (IGI Global, 2023)
This chapter analyzes the key arguments as explored by previous researchers on coping strategies applied by first-year students transitioning to institutions of higher education. The majority of first-year students face various challenges in adjusting to college life. New students use their peer group as a source of their company, sympathy, affection, and experimentation, which can be either productive or wasteful. Quite a good number of students use negative coping strategies to eliminate the psychological pressures evoked by the situations they find themselves. Being aware of one’s strengths and weaknesses can aid one in choosing the best coping strategies. Having self-control, acceptance of individual differences, and positive thinking would contribute to an individual’s coping strategies. The recommendation is that the universities assign new students to individual peer guides and advise students on how to go about the university dynamics by getting involved in positive leisure activities such as sports, getting into serious peer study groups, and social networking.
Risk Factors for the Adjustment of First-Year Students
16 more pages are available in the full version of this document, which may be purchased using the "Add to Cart" button on the product's webpage: www.igi-global.com/chapter/risk-factors-for-the-adjustment-of-first-yearstudents/319250?camid=4v1